Hydrodynamics of trickle-bed reactors: experiments and CFD modeling - Gunjal, P. R.; Kashid, M. N.; Ranade, V. V.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2005)
{Hydrodynamics of trickle-bed reactors involve complex interactions of gas and liquid phases with packed solids. Such complex interactions manifest in different flow regimes occurring in trickle-bed reactors. Knowledge of prevailing flow regime, pressure drop, and liquid holdup is essential for design and performance evaluation of the reactor. Detailed knowledge of fluid dynamics is essential for ``a priory'' predictions as well as for interpretation of available data. In this study, we have used wall pressure fluctuation measurements to identify prevailing flow regime in trickle beds. Experiments were carried out on two scales of columns (of diameter 10 cm and 20 cm) with two sets of particles (3 min and 6 mm diameter spherical particles). Effects of prewetted and unwetted bed conditions on pressure drop and liquid holdup were reported for a range of operating conditions (V-G = 0.22-0.44 kg/m(2)s